Tauhid Emansipatoris sebagai Rekonstruksi Epistemologi Tazkiyatun Nafs: Dari Asketisme Individual menuju Paradigma Transformatif ilmu dan pembebasan sosial - The End Tri Hasnawati Favorita; Anandita Eka Islamadina; Azizah Tuz Zahra; Ali Hasan Hasan Siswanto (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
The multidimensional crisis of modern humanity—marked by dehumanization, spiritual fragmentation, and the dominance of secular paradigms—has weakened the relationship between knowledge and transcendental values. In this context, tazkiyatun nafs is still often understood in a reductionistic manner as merely an individual ascetic practice, thus failing to respond to structural problems and contemporary social crises. The research gap lies in the absence of an integrative and transformative epistemological formulation of tazkiyatun nafs, one that positions tauhid as the foundation for scientific and social emancipation. This article aims to reconstruct tazkiyatun nafs through the theoretical approach of emancipatory tauhid, which integrates theological, philosophical, and socio-critical dimensions. This approach positions tauhid not merely as a normative doctrine, but as an ontological and axiological principle for the liberation of humanity from various forms of non-divine domination. The research method employed is qualitative-conceptual, using philosophical-critical analysis and a hermeneutic approach to classical Sufi literature as well as contemporary thought. The main argument of this article asserts that tazkiyatun nafs needs to be reconstructed from a self-purification orientation toward a transformative paradigm that integrates personal purification with social change. Thus, emancipatory tauhid functions as an epistemological foundation for the development of holistic knowledge oriented toward human liberation. The scientific contribution of this study lies in offering a new paradigm in Islamic Studies that integratively connects spirituality, rationality, and social praxis, while also opening space for the development of a transformative human model within the framework of contemporary Islamic scholarship.